The Supreme Court of Nova Scotia, 1754-2004 : from imperial bastion to provincial oracle - Girard, Philip; Phillips, Jim; Cahill, Barry (Osgoode Society for Canadian Legal History series., 2004)
"Prepared to coincide with the 250th anniversary of the establishment of Nova Scotia's Supreme Court, this volume provides a wide-ranging history of the institution, Canada's oldest common law court. The thirteen essays include an account of the first meeting in 1754 of the court in Michaelmas Term; surveys of jurisprudence covering such topics as the court's early federalism cases, its use of American law, and attitudes to the administrative state; and chapters on the courts of Westminster Hall, on which the Supreme Court was modelled, and the various courthouses it has occupied. Comprehensive introductory chapters on the pre-confederation and modern periods provide a contextual framework for the volume."--Jacket.